The Cell Differentiation of Idioblast Myrosin Cells: Similarities With Vascular and Guard Cells - Shirakawa, Makoto; Tanida, Mai; Ito, Toshiro (Frontiers in Plant Science, 2022)
Idioblasts are defined by abnormal shapes, sizes and contents that are different from neighboring cells. Myrosin cells are Brassicales-specific idioblasts and accumulate a large amount of thioglucoside glucohydrolases (TGGs, also known as myrosinases) in their vacuoles. Myrosinases convert their substrates, glucosinolates, into toxic compounds when herbivores and pests attack plants. In this review, we highlight the similarities and differences between myrosin cells and vascular cells/guard cells because myrosin cells are distributed along vascular cells, especially the phloem parenchyma, and myrosin cells share the master transcription factor FAMA with guard cells for their cell differentiation. In addition, we analyzed the overlap of cell type-specific genes between myrosin cells and guard cells by using published single-cell transcriptomics (scRNA-seq) data, suggesting significant similarities in the gene expression patterns of these two specialized cells.